Buried in treasures : help for compulsive acquiring, saving, and hoarding - Tolin, David F.; Frost, Randy O.; Steketee, Gail (Treatments that work., 2014)
While most people find it relatively easy to manage their possessions, some find it extremely difficult. If you have a problem resisting the urge to acquire and you find your home cluttered and filled to capacity with items many people would find useless and unnecessary, you may suffer from a condition known as hoarding disorder.